PUBLIC RELATIONS STRATEGY OF THE ASSET RECOVERY AGENCY OF THE ATTORNEY GENERAL’S OFFICE OF THE REPUBLIC OF INDONESIA IN SOCIALIZING STATE CONFISCATED GOODS AUCTIONS ON DIGITAL MEDIA - Salsabila Azzahra; Farhan Indra (Journal Analytica Islamica, 2026)
This study analyzes the public relations strategy of the Attorney General's Office of the Republic of Indonesia's Asset Recovery Agency in promoting the auction of state-confiscated assets through digital media. This study is important because promoting the auction of state-confiscated assets requires not only rapid information dissemination but also a transparent, educational communication strategy that encourages public participation. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, non-participatory observation of official digital media, and documentation of the agency's publications. Research informants included the Asset Recovery Agency's digital media managers, internal parties, and the public as the audience for the auction information. The results show that the digital public relations strategy was implemented through the stages of planning, implementation, and evaluation of communications. The digital media used included Instagram, the website, and Facebook, with Instagram as the primary channel due to its visual character, broad audience reach, and segmentation features through insights and digital advertising. The messages conveyed were informative and educational, particularly regarding the type of goods, prices, locations, procedures, and auction conditions. The findings also indicate the practice of two-way communication through comments, direct messages, and WhatsApp contacts, although the reach of information and the quality of public interaction still need to be strengthened. This study confirms that digital public relations strategies play an important role in increasing transparency, public understanding, and public trust in the management of state confiscated assets.